A strategic plan for Durian Services, Inc. - Ledesma, Karina Angelica Julia S.; Soledad, Miguel D.; Concepcion, Sylvia B. (Davao City School of Management, University of the Philippines Mindanao, 2010)
Durian Citiservices, Inc. is a service company engaged in manpower job contracting and other allied services. Since 1997, it has deployed manpower personnel in various business establishment all throughout Mindanao. At present, the company has no clearly laid out strategies in place, and basically play by ear. DCI?s 2008 financial performance compared year on year versus 2007 has decreased although only marginally so. As of the last year, the major operational highlight is the increase in the number of manpower personnel roster to 217employees. This implies that the number of clients or the number of client requirement is increasing, giving additional business to DCI. The conceptual framework employed was an adaptation of David?s (2008) strategic management framework. Data was gathered from both primary and secondary sources. The external and internal analyses show that DCI has an average ability to respond to its external environment, and it is internally strong. Its strengths include organizational structure suitability, fast decision-making, above average economic benefits, area coverage-majority of the Mindanao area, debt-free, generally increasing ROE, and availability of various communications channels. In contrast, its weaknesses are low formalization, absence of job descriptions and employment contracts, reliance on word-of-mouth promotion, relatively flat ROS, decreasing growth of gross income, and a General Manager performing a multitude of functions. Its opportunities are catering to the overseas market, computerization and automation, utilization of highly technological networking channels, tapping the BPO, real estate and tourism markets, developing a CSR program, having lesser competition, and exploring markets outside of Davao and Mindanao. Its threats, on the other hand, include decrease in number of potential employees, cost of systems automation, pressure from employees for economic benefits, constant increase in labor cost, and possible price war within industry players. It is integral that DCI is guided with strategic goals. Thus, in the next five years, the suggested long-term objectives for DCI are: 1)to increase manpower complement by 80 staff every year for the next five years (2010-2014); 2)to increase gross income by at least 30% in 2010 with increments of 5% annually in the succeeding years: 3)to draft policies and procedures that serve as guidelines for decision making, allow consistency and coordination within the organization. The proposed strategies are market penetration and product leadership. A five-year plan was presented with the intention to concentrate on a particular market niche and exploit their expertise in this market and to concentrate on achieving superior performance in an important customer benefit area valued by a large part of the market. A detailed action plan is presented showing the implementing activities to be carried out in each functional area. In order to serve as control measures, the key result areas, performance indicators and strategic evaluation framework are presented. In addition, a risk management and contingency plan is also provided.
Thesis (Master in Management)--University of the Philippines Mindanao, April 2010.